Managing Motherhood: Job Context and Employer Bias. Issue 2 (May 2018) - Glass, Christy; Fodor, Eva
How does job context influence employers' views of mothers as workers? Drawing on 51 in-depth interviews with employers in the finance and business service sectors of Hungary, the authors find that finance employers rely on a variety of strategies aimed at excluding mothers from entry-level professional jobs, while business services employers invest significant resources aimed at recruiting and accommodating mothers. To explain this variation, the authors suggest that employers' views of mothers are dependent on their perception of skill requirements and knowledge/skill dynamism.